High-grade Gliomas Exhibit Higher Peritumoral Fractional Anisotropy and Lower Mean Diffusivity than Intracranial Metastases - Holly, Kevin S.; Barker, Benjamin J.; Murcia, Derrick; Bennett, Rebekah; Kalakoti, Piyush; Ledbetter, Christina; Gonzalez-Toledo, Eduardo; Nanda, Anil; Sun, Hai (Frontiers in Surgery, 2017)
Differentiating high grade gliomas and intracranial metastases through noninvasive imaging has been challenging. Here we retrospectively compared both intratumoral and peritumoral fractional anisotropy (FA), mean diffusivity (MD) and fluid-attenuated inversion recovery (FLAIR) measurements between high grade gliomas and metastases. Two methods were utilized to select peritumoral region of interest (ROI). The first method utilized the manual placement of four ROIs adjacent to the lesion. The second method utilized a semi-automated and proprietary MATLAB script to generate a ROI encompassing the entire tumor. The average peritumoral FA, MD, and FLAIR values were determined within the ROIs for both methods. Forty patients with high grade gliomas and 44 with metastases were enrolled in this study. Thirty-five patients with high grade glioma and 30 patients with metastases had FLAIR images. There was no significant difference in age, gender, or race between the two patient groups. The high grade gliomas had a significantly higher tumor-to-brain area ratio compared to the metastases. There were no differences in average intratumoral FA, MD and FLAIR values between the two groups. Both the manual sample method and the semi-automated peritumoral ring method resulted in significantly higher peritumoral FA and significantly lower peritumoral MD in high grade gliomas compared to metastases (p < 0.05). No significant difference was found in FLAIR values between the two groups peritumorally. Receiver operating curve (ROC) analysis revealed FA to be a more sensitive and specific metric to differentiate high grade gliomas and metastases than MD. The differences in the peritumoral FA and MD values between high grade gliomas and metastases seemed due to the infiltration of glioma to the surrounding brain parenchyma.